Mimicking the neural stem cell niche: An engineer’s view of cell: material interactions - Yazdani, Narges; Willits, Rebecca Kuntz (Frontiers in Chemical Engineering, 2023)
Neural stem cells have attracted attention in recent years to treat neurodegeneration. There are two neurogenic regions in the brain where neural stem cells reside, one of which is called the subventricular zone (SVZ). The SVZ niche is a complicated microenvironment providing cues to regulate self-renewal and differentiation while maintaining the neural stem cell’s pool. Many scientists have spent years understanding the cellular and structural characteristics of the SVZ niche, both in homeostasis and pathological conditions. On the other hand, engineers focus primarily on designing platforms using the knowledge they acquire to understand the effect of individual factors on neural stem cell fate decisions. This review provides a general overview of what we know about the components of the SVZ niche, including the residing cells, extracellular matrix (ECM), growth factors, their interactions, and SVZ niche changes during aging and neurodegenerative diseases. Furthermore, an overview will be given on the biomaterials used to mimic neurogenic niche microenvironments and the design considerations applied to add bioactivity while meeting the structural requirements. Finally, it will discuss the potential gaps in mimicking the microenvironment.